MONOMINERALIC MOBILIZATION OF PLAGIOCLASE BY SHOCK: AN EXPERIMENTAL STUDY - Yamaguchi A.; Sekine T. (My University, 2000)
Shock recovery experiments of plagioclase feldspar in contact with pyroxene, shock-loaded at 36-53 GPa, showed that monomineralic glass of plagioclase was mixed with brecciated pyroxenes with virtual absence of mixed-mineral melts. This amorphous phase of plagioclase produced at 36-42 GPa displays enormously high ductility although the amorphous phase is less likely to be a quenched high-pressure melt because both shock and post-shock bulk temperature cannot exceed the melting point. The results suggest that alkaline components in feldspar can be extensively mobilized even in a very short duration of shock, which can never be achieved by normal diffusion in the same time scale. Since feldspar is a major carrier phase of alkaline volatiles, shock mobilization mechanism may explain shock disturbance of Rb-Sr and 39Ar-40Ar ages of basaltic shergottites.
Keywords: PLAGIOCLASE; SHOCK METAMORPHISM; MOBILIZATION; SHERGOTTITE; EXPERIMENTAL STUDIES